The Impact of Business Process Reengineering in the institutional performance : Research in the office of the General Inspector in the Ministry of Higher Education and Scientific Research - اللامي, غسان داود; كاظم, باسم حاكم (Journal of Economics and Administrative Sciences, 2016)
Abstract       This research is aimed at indicating the impact of business process reengineering on corporate performance in the Office of the Inspector General of the Ministry of Higher Education and Scientific Research of the Iraqi study has identified a problem in a number of the most important questions - what the impact of the Business Process Reengineering at the corporate office performance indicators respondent? What are the actual results of the analysis of paths Administrative Process Engineering and Corporate Performance respondent in the office? In order to achieve the goal of the research and answer the questions of the problem, the study applied to a sample of (60) a member of the office staff out of (127) and functional level extends between managers and department heads and officials of the people and officials of the units and some of the staff, has used the questionnaire as a tool to collect data and information . And achieved Find a set of results, highlighted by the presence of significant moral correlation between Business Process Reengineering and the dimensions of corporate performance show that there is significant effect between Business Process Reengineering and the dimensions of organizational performance and identify the bugs found in the course of the office operations.